Aktivitas Cendawan Antagonis Trichoderma terhadap Fusarium dari Tanaman Kentang di Kecamatan Pakis Kabupaten Magelang - Susiana Purwantisari; Wahyu Aji Mahardhika; Mochammad Faiq Qoys Naufal; Arina Tri Lunggani; Siti Nur Jannah (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Potato is one of the common plants cultivated in Indonesia and used as a food ingredient besides rice. One of the pathogens that can attack potatoes is Fusarium. Farmers usually use synthetic fungicides to inhibit Fusarium infection, but this method is not environmentally friendly. One of the countermeasures for Fusarium can be done with the antagonistic fungus Trichoderma. This study aims to examine the antagonistic of Trichoderma spp. toward isolate Fusarium spp. from potato plants showing wilting symptoms. The method was carried out by isolating the fungus from potatoes with wilting symptoms, identifying it, and testing 4 Trichoderma strains using a double culture method. The fusarium obtained was identified as F. begoniae, F. foetens, F. mooniliforme, and F. oxysporum. A total of 2 Trichoderma strains originating from litter and trash cans were able to inhibit all Fusarium tests on day 2 and achieve 100% growth inhibition on day 4, while the other 2 Trichoderma strains only showed inhibition on day 4 to day 7. Further tests are needed to understand the mechanism of Fusarium attack, and to identify the antifungal compounds produced by Trichoderma.